2021
DOI: 10.1016/j.atherosclerosis.2021.09.010
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis on the effects of statins on pregnancy outcomes

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…However, patient' responses to TLC varied, and poor adherence to this therapeutic protocol was cited as one of its drawbacks [11,12]. Furthermore, the administration of statins in patients with elevated serum LDL-C is the first-line pharmacological treatment and effectively reduces total cholesterol (TC) and LDL-C levels [13][14][15]. However, some adverse events such as muscle-related symptoms, increased liver enzyme transaminase, elevated blood glucose, and glycated hemoglobin levels have been reported [14,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…However, patient' responses to TLC varied, and poor adherence to this therapeutic protocol was cited as one of its drawbacks [11,12]. Furthermore, the administration of statins in patients with elevated serum LDL-C is the first-line pharmacological treatment and effectively reduces total cholesterol (TC) and LDL-C levels [13][14][15]. However, some adverse events such as muscle-related symptoms, increased liver enzyme transaminase, elevated blood glucose, and glycated hemoglobin levels have been reported [14,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…However, pravastatin is also believed to have pleiotropic effects as anti-inflammatory, anti-oxidant, anti-thrombotic, pro-angiogenic, and protective of the endothelium. 16 This study aims as one of the initial studies to explore the potential of pravastatin against functional abnormalities or placental hypoxia through in vivo HIF-1-A expression.…”
Section: Introductionmentioning
confidence: 99%
“…This was endorsed worldwide, including in recent statements by the National Lipid Association and the International Familial hypercholesterolemia Foundation [3,4]. However, more than three decades of experience with accidental statin use, immediately before and during pregnancy, did not corroborate these initial concerns [3,[5][6][7]. Further, recent well-performed large observational cohort studies have not substantiated any teratogenic effect of statins [8].…”
mentioning
confidence: 99%
“…A Medicaid cohort study compared 1,152 statinexposed pregnant women to 886,996 matched controls but reported no teratogenic effects from maternal use of statins in the first trimester of pregnancy -after adjustment for potential confounders [15]. A recent meta-analysis of 9 observational studies found no association between statin use and stillbirth (OR 1.30; 95% CI 0.56-3.0; p=0.54), induced abortion (OR 2.08; 95% CI; 0.81-5.36; p=0.129), or elective abortion (OR 1.37; 95% CI, 0.68-2.76; p=0.378) [5] but spontaneous abortion was more common (OR 1.36; 95% CI, 1.10-1.68; p=0.004). More recently, a retrospective cohort study of 469 statin-exposed pregnant women (vs. 4,690 matched controls) reported no increase in congenital anomalies (RR, 1.24; 95% CI 0.81-1.90 after adjustment for maternal age and comorbidities), although there was a greater risk of low birth weight (RR 1.51; 95% CI, 1.05-2.16) and preterm birth (RR 1.99; 95% CI, 1.46-2.71) [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation